2023
DOI: 10.3390/polym15030542
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Sustained Release Curcumin-Loaded Solid Lipid Nanoparticles (Cur-SLNs) as a Potential Drug Delivery System for the Treatment of Lung Cancer: Optimization of Formulation and In Vitro Biological Evaluation

Abstract: The goal of current research was to develop a new form of effective drug, curcumin-loaded solid lipid nanoparticles (Cur-SLNs) and test its efficacy in the treatment of lung cancer. Different batches of SLNs were prepared by the emulsification–ultrasonication method. For the optimization of formulation, each batch was evaluated for particle size, polydispersity index (PI), zeta potential (ZP), entrapment efficiency (EE) and drug loading (DL). The formulation components and process parameters largely affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Therefore, these results certified that the PLGA NPs, when resorting to proper storage conditions, were efficient to preserve CUR even after 1 year. This provides important information on the shelf life of these nanoformulations, complementing previous studies that evaluated storage stability up to 6 months initially. , …”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, these results certified that the PLGA NPs, when resorting to proper storage conditions, were efficient to preserve CUR even after 1 year. This provides important information on the shelf life of these nanoformulations, complementing previous studies that evaluated storage stability up to 6 months initially. , …”
Section: Resultssupporting
confidence: 57%
“…This provides important information on the shelf life of these nanoformulations, complementing previous studies that evaluated storage stability up to 6 months initially. 58,59 3.7. Toxicity Studies.…”
Section: Chemical Mapping Via Atomic Force Microscopy-mentioning
confidence: 99%
“…Exploring compounds derived from nature, such as polyphenols and terpenoids, introduces potential anticancer properties with lower toxicity profiles. Curcumin [62][63][64][65][66] and other polyphenols exhibit anti-inflammatory and anticancer effects. Terpenoids like oridonin [67,68] and other natural extracts have shown efficacy against various cancer mechanisms.…”
Section: Natural-based Treatmentsmentioning
confidence: 99%
“…The findings indicated that these Cur-SLNs exhibited higher cytotoxicity against lung cancer cells compared to free curcumin, with significant uptake by the cells. This suggests that the solid lipid nanoparticles enhance the delivery and efficacy of curcumin, making it more effective in targeting and killing cancer cells [63]. Further exploring the applications of curcumin, solid lipid nanoparticles loaded with curcumin were characterized for their physicochemical properties and analyzed for anticancer efficiency both in vitro and in vivo, with a particular emphasis on apoptosis induction.…”
Section: Polyphenolsmentioning
confidence: 99%
“…Curcumin was found to inhibit cell growth in HCT-116 and HT29 colon cancer cell lines. 180 , 181 It interacts with many targets and thus influences key signaling pathways related to colon cancer, such as receptor tyrosine kinase (RTK) signaling, Wnt signaling pathway, Notch signaling, and p53 pathway. Resveratrol, a natural phenol derived from grapes, raspberries, and mulberries, is another phytochemical with anti-colon cancer potential.…”
Section: Recent Update On Personalized Therapeutics In Perspective Of...mentioning
confidence: 99%